(untitled) (ModaPalavra e-periódico, 2009)
This article is proposed to investigate the condition of mass consumption in contemporary society and its relations with fashion and individuals that society. Based on theoretical publications on the subject, discusses the development of consumption with the changes incurred by the society until his condition and spectacularization as supplier for the articulation of appearances. Factor of extreme importance in the fashion system, the consumption is more complex than a trade in objects, he presents himself as an exchange of symbols and allocation of values. Amid the processes of massification, the own mass consumption because of its diversity and scope, becomes a tool of individualization, through consumer choice. Ally the search for pleasure or happiness, working in constant motion, cyclical, ephemeral, together with the power of fashion, awakening desire, which returns to boost the movement of the news.